Reaction of Lithiated Propargyl Ethers with Carbonyl Compounds – A Regioselective Route to Furan Derivatives - Linder, Igor; Klemme, Robby; Reissig, Hans-Ulrich (Synthesis, 2020)
The deprotonation of 3-aryl-substituted alkyl propargyl ethers with n-butyllithium provides an ambident anion that reacts with carbonyl compounds to provide mixtures of γ-substituted products with alkoxyallene substructure and of α-substituted propargyl ethers. The ratio of the two product types strongly depends on the solvent: in diethyl ether the γ-substituted products predominate whereas the more polar tetrahydrofuran favors the α-adducts. The primary addition products undergo 5-endo-trig or 5-endo-dig cyclizations under various reaction conditions to afford isomeric furan derivatives. The highest selectivity in favor of α-substituted products was achieved by employing a MOM-protected propargyl ether. During the protonation step no evidence for a proton shift leading to an isomeric allenyl anion was found. A brief mechanistic discussion tries to rationalize the observed regioselectivities.
Keywords: alkoxyallene; alkyne; cyclization; furan; gold catalysis; lithiation; regioselectivity; silver catalysis